Prevention and management of pain and stress in the neonate - Harrison D; Bueno M; Reszel J (Dove Medical Press, 2015)
Denise Harrison,1,2 Mariana Bueno,3 Jessica Reszel2 1School of Nursing, University of Ottawa, Ottawa, ON, Canada; 2Children's Hospital of Eastern Ontario and Children's Hospital of Eastern Ontario Research Institute, Ottawa, ON, Canada; 3Department of Maternal Child and Psychiatric Nursing, School of Nursing, University of São Paulo, São Paulo, Brazil Abstract: Neonates have blood work for newborn screening in their first days of life, and preterm and sick hospitalized infants often require repeated invasive needle-related procedures over the duration of their hospitalization. Reducing newborn infants' pain during such painful procedures is important and may reduce the risk of negative sequela of poorly treated procedural pain. High-quality synthesized evidence demonstrates analgesic effects of three pain management strategies: breastfeeding; skin-to-skin care, also referred to as kangaroo care; and small amounts of sweet solutions. These strategies are simple to use, easily accessible, and extremely cost-effective. Published neonatal and infant pain guidelines include recommendations to use these strategies prior to and during painful procedures. Yet, despite the robust evidence and pain management recommendations in guidelines and national and international organizations, knowledge has not been translated into consistent normalized care in diverse maternal newborn, neonatal, and pediatric settings where painful procedures for infants take place. There may be knowledge gaps or barriers impeding consistent use of effective pain management for newborn infants. This paper will present a brief review of methods used to assess neonatal pain, followed by a summary of the evidence supporting breastfeeding, skin-to-skin care, and sweet solutions for procedural pain reduction with a discussion about barriers and facilitators to using these strategies in the clinical setting. Finally, a review of recommendations included in current neonatal pain guidelines will be presented. Keywords: infant, pain management, breastfeeding, skin-to-skin care, sucrose